In Vivo Kidney Allograft Endothelial Specific Scavengers for On‐Site Inflammation Reduction under Antibody‐Mediated Rejection. Issue 36 (2nd March 2022) - Liu, Chang; Yan, Pengpeng; Xu, Xiaoyu; Zhou, Wenhui; Prakash, Dhayakumar Rajan; Wang, Shuqi; Zhou, Junnian; Wang, Rending; Huang, Hongfeng; Chen, Jianghua; Zhang, Hongbo; Shen, Jia
Abstract: Kidney transplantation is the most effective therapy for patients with end‐stage renal disease. However, antibody‐mediated rejection (ABMR) threatens long‐term survival of renal grafts. Although ABMR can be controlled by donor‐specific antibody clearance and B‐ or (and) plasma‐cells inhibition, the treatment often causes severe side effects in patients. Therefore, there is need to explore site‐specific scavengers. In this study, a nanovehicle carrying an anti‐inflammatory drug is developed with complement component 4d targeting, a specific biomarker expressed on allograft endothelium under ABMR. Moreover, the nanovehicle is endowed with photothermal properties to control drug release. Analysis through systematic in vitro and in vivo toxicity, non‐invasive targeted imaging, and in situ remote controlled drug release show the nanovehicle specifically targets allograft kidney endothelium, releases an anti‐inflammatory drug, methylprednisolone, locally upon laser irradiation, and promotes recovery of injured endothelium, without affecting systemic inflammation or innate immune responses. This strategy has the potential for future clinical application in ABMR treatment. Abstract : A nano‐delivery platform that targets damaged endothelium caused by antibody‐mediated rejection after kidney transplantation is presented. Non‐invasive stimuli‐responsive drug release can reduce systemic inflammation and innate immune responses while promoting recovery of injured endothelium.